Bioactive Marine Heterocyclic Compounds - Usami, Yoshihide (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue of Marine Drugs, entitled "Bioactive Marine Heterocyclic Compounds", aimed to collect excellent original research articles and reviews focused on the isolation of new heterocyclic marine natural products, total synthesis, synthetic modification, or on finding important bioactivities of known heterocyclic marine natural products. As a result, five original papers on isolation and one synthetic study of metabolites from marine-derived bioorganisms or a marine sponge, along with one review paper on thiazole-based peptides, were published. I am proud to show these most recent works of outstanding scientists in this field and hope this Special issue will affect new drug developments or innovation in the future.